2013
DOI: 10.1182/blood-2012-11-467191
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of sphingosine-1-phosphate receptor 2 (S1PR2) in acute vascular inflammation

Abstract: • Endothelial S1PR2 plays a critical role in the induction of vascular permeability and vascular inflammation during endotoxemia.• S1PR2 could be a novel therapeutic target to promote vascular integrity in inflammatory vascular disorders.The endothelium, as the interface between blood and all tissues, plays a critical role in inflammation. Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid, highly abundant in plasma, that potently regulates endothelial responses through interaction with its receptors (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
130
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 45 publications
15
130
2
1
Order By: Relevance
“…The pro-infl ammatory tendency of S1P 2 is supported by in vitro studies suggesting a paracrine feedback loop involving EC TNF ␣ induction of S1P 2 expression leading to activation of nuclear factor (NF)-B and increases in intracellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 ( 61 ). In vivo studies utilizing S1pr2 Ϫ / Ϫ mice and a model of acute infl ammation, endotoxemia, further support the conclusion that S1P 2 is an important regulator of vascular activation and therefore, permeability ( 62 ). Induction of endotoxemia in mice lacking S1pr2 in the stroma and not in the bone marrow (BM) compartment resulted in decreased vascular permeability, VCAM-1 and ICAM-1 expression, and more rapid resolution ( 62 ).…”
Section: Immune Systemmentioning
confidence: 62%
See 1 more Smart Citation
“…The pro-infl ammatory tendency of S1P 2 is supported by in vitro studies suggesting a paracrine feedback loop involving EC TNF ␣ induction of S1P 2 expression leading to activation of nuclear factor (NF)-B and increases in intracellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 ( 61 ). In vivo studies utilizing S1pr2 Ϫ / Ϫ mice and a model of acute infl ammation, endotoxemia, further support the conclusion that S1P 2 is an important regulator of vascular activation and therefore, permeability ( 62 ). Induction of endotoxemia in mice lacking S1pr2 in the stroma and not in the bone marrow (BM) compartment resulted in decreased vascular permeability, VCAM-1 and ICAM-1 expression, and more rapid resolution ( 62 ).…”
Section: Immune Systemmentioning
confidence: 62%
“…In vivo studies utilizing S1pr2 Ϫ / Ϫ mice and a model of acute infl ammation, endotoxemia, further support the conclusion that S1P 2 is an important regulator of vascular activation and therefore, permeability ( 62 ). Induction of endotoxemia in mice lacking S1pr2 in the stroma and not in the bone marrow (BM) compartment resulted in decreased vascular permeability, VCAM-1 and ICAM-1 expression, and more rapid resolution ( 62 ). Similarly, in vitro, S1P 2 actively suppressed angiogenic sprouting through leukemia-associated RhoGEF (LARG) activation of RhoC ( 63 ).…”
Section: Immune Systemmentioning
confidence: 69%
“…S1PRs are GPCRs expressed in endothelium and other tissues that regulate cell survival, adherens junction assembly, migration, and barrier integrity (61-63). Several studies have indicated their role in vascular biology (64)(65)(66). Using the EAE mouse model for human MS, Cruz-Orengo and colleagues recently suggested a role for S1PR2 in MS (60).…”
mentioning
confidence: 99%
“…In contrast, in their counterpart A7 melanoma cells that express FLNA, S1P does not activate NF-B unless the expression of FLNA is downregulated. Several previous reports suggested that S1P can activate NF-B via S1PRs (14,15,(29)(30)(31)(32)(33)(34). Although in some studies, the S1PR involved was not identified and the concentration of S1P used was too high to substantiate the involvement of S1PR-mediated events (35), others have clearly implicated S1PR1 to -3 in different cell types.…”
Section: Discussionmentioning
confidence: 75%
“…However, in HeLa cells, S1PR2, but not S1PR1 or S1PR3, was responsible for the activation of NF-B induced by extracellular S1P (14). In addition, S1PR2 induced endothelial inflammation by the activation of the Rho-ROCK (Rho-associated protein kinase) pathway leading to NF-B activation (34). Using M2 mela- noma cells, we have now provided evidence showing that both S1PR1 and S1PR2 are involved in the activation of NF-B by S1P.…”
Section: Discussionmentioning
confidence: 99%